2016
DOI: 10.1128/jcm.01242-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Identification of KPC-Producing Klebsiella pneumoniae

Abstract: dWe evaluated a real-time single-peak (11.109-Da) detection assay based on matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the identification of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae. Our results demonstrated that the 11.109-Da peak was detected in 88.2% of the KPC producers. Analysis of bla KPCproducing K. pneumoniae showed that the gene encoding the 11.109-Da protein was commonly (97.8%) associated with the Tn4401a isoform. In the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Recently, a specific peak at 11,109 m/z, related to a pKpQIL plasmid carrying bla KPC was discovered in the MALDI-TOF mass spectra of KPC-producing Klebsiella pneumoniae ( Lau et al, 2014 ). Different approaches to seek for this peak have been described ( Lau et al, 2014 ; Gaibani et al, 2016 ; Youn et al, 2016 ). Nevertheless all of them required a second step after routine species identification process like visual inspection or an additional software analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a specific peak at 11,109 m/z, related to a pKpQIL plasmid carrying bla KPC was discovered in the MALDI-TOF mass spectra of KPC-producing Klebsiella pneumoniae ( Lau et al, 2014 ). Different approaches to seek for this peak have been described ( Lau et al, 2014 ; Gaibani et al, 2016 ; Youn et al, 2016 ). Nevertheless all of them required a second step after routine species identification process like visual inspection or an additional software analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This specific peak at 11,109 m/z is clearly detectable in bacterial MALDI-TOF mass spectra. Different approaches to seek for this peak have been used and evaluated ( Lau et al, 2014 ; Gaibani et al, 2016 ; Youn et al, 2016 ). Until recently, the detection of this peak required a manual operation, with visual analysis or additional software in a second step after the routine identification process, and therefore impeding a real-time detection of KPC strains ( Lau et al, 2014 ; Gaibani et al, 2016 ; Youn et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the identification of a 11 109 Da MS peak corresponding to a gene product of the bla KPC pKpQIL plasmid was found to be useful in rapid tracking KPC-producing strains [13].…”
mentioning
confidence: 99%
“…Further genetic analysis revealed that the 4 strains negative for the 11.109 m/z peak could be explained by different isoforms of Tn 4401 . Only TN 4401a is commonly associated with the 11.109 m/z peak (Gaibani et al, 2016 ). In 2018 the same group published a study on 140 well-characterized K. pneumoniae strains collected between 2011 and 2017 and found an overall accuracy of 98%, a positive predictive value of 98% and a negative predictive value of 97% (Gaibani et al, 2018 ).…”
Section: Assays Using Defined Marker Peaks To Deduce Susceptibility Omentioning
confidence: 99%